Vitamin D alleviates non-alcoholic fatty liver disease via restoring gut microbiota and metabolism - Zhang, Xiao-Lei; Chen, Lei; Yang, Jiang; Zhao, Shan-Shan; Jin, Shi; Ao, Na; Yang, Jing; Liu, Hui-Xin; Du, Jian (Frontiers in Microbiology, 2023)
Non-alcoholic fatty liver disease (NAFLD) represents a severe public health problem. Dysbiosis of gut microbiome has been identified as one of the key environmental factors contributing to NAFLD. As an essential nutrition, Vitamin D (VD) plays an important role in regulating gut microbiota, and its receptor (Vitamin D Receptor, VDR) is highly expressed in the gastrointestinal tract. Herein, we investigated the beneficial effects of VD on NAFLD by regulating the gut microbiota and metabolism. We discovered the VD alleviates the HFD induced lipid accumulation in the liver as well as decreased the levels of amlodipine besylate (ALT) and amlodipine aspartate (AST). VD supplement decreased the ratio of phylum Firmicutes/Bacteroidetes (F/B) but increased alpha diversity. In addition, the VD treatment improved the high fat diet (HFD) induced gut microbiota by increasing the Prevotella, Porphyromonadaceae and decreasing Mucispirillum, Acetatifactor, Desulfovibrio, Oscillospira abundance. Furthermore, the capability of tyrosine metabolism, tryptophan metabolism, arginine biosynthesis and sphingolipid metabolism were enhanced after VD treatment. Consistently, Prevotella positively correlated with tryptophan metabolism and sphingolipid metabolism. Importantly, the Prevotella abundance was positively associated with serotonin, melatonin, tryptamine, L-arginine, and 3-dehydrosphinganine which synthesis from tryptophan, tyrosine, arginosuccinate, and serine, respectively. In summary, our results show that VD supplement could be a potential intervention used for NAFLD treatment by targeting the specific microbiota.